Evidence for direct CP violation in the measurement of the Cabbibo-Kobayashi-Maskawa angle γ with B∓→D(*)K(*)∓ decays - Amo Sanchez, Pablo del; Adametz, Aleksandra; Marks, Jörg; Schenk, Sebastian; Uwer, Ulrich; Hartmann, Thomas; Leddig, Torsten; Schröder, Henning; Waldi, Roland (Physical review letters, 2010)
We report the measurement of the Cabibbo-Kobayashi-Maskawa CP-violating angle γ through a Dalitz plot analysis of neutral D-meson decays to K0Sπ+π− and K0SK+K− produced in the processes B∓→DK∓, B∓→D∗K∓ with D∗→Dπ0, Dγ, and B∓→DK*∓ with K*∓→K0Sπ∓, using 468 million B¯¯¯B pairs collected by the BABAR detector at the PEP-II asymmetric-energy e+e− collider at SLAC. We measure γ=(68±14±4±3)° (modulo 180°), where the first error is statistical, the second is the experimental systematic uncertainty, and the third reflects the uncertainty in the description of the neutral D decay amplitudes. This result is inconsistent with γ=0 (no direct CP violation) with a significance of 3.5 standard deviations.